Masjid Kasunyatan Dan Makam Maulana Yusuf Sebagai Wisata Religi - Asfiana Adyani Nastiti; Fatimah Nabiela Nakhla; Herlian Susanto; Faris Sauqi Syahid; Torik Useng; Abd Rahman Hamid; Agus Mahfudin Setiawan (FIHROS: Jurnal Sejarah dan Budaya, 2025)
This article discusses two important historical sites in the Banten region, namely the Kasunyatan Mosque and the Tomb of Maulana Yusuf, which have high spiritual, cultural, and historical value. The Kasunyatan Mosque, built in the 16th century by Kyai Dukuh, became a symbol of Islamic preaching as well as a center of religious education during the Banten Sultanate. The mosque's distinctive architecture and layout, rich in philosophical values, reflect a blend of Islamic traditions and local culture. Meanwhile, the Maulana Yusuf Mausoleum stands as a testament to the significant role of the second sultan of the Banten Sultanate in conquering Pajajaran and expanding Islamic influence. The mausoleum's proximity to his spiritual mentor symbolizes the harmony between political power and religious authority during that era. Today, both sites have developed into popular religious tourism destinations, especially during major Islamic holidays. Through historical research methods, this article demonstrates that the Kasunyatan Mosque and Maulana Yusuf's Tomb not only hold religious significance but also possess profound historical, social, and cultural value, and have the potential to be developed as religious tourism sites rooted in local culture.